2020
DOI: 10.1364/ao.384782
|View full text |Cite
|
Sign up to set email alerts
|

Conception of diffractive wavefront correction for XUV and soft x-ray spectroscopy

Abstract: We present a simple and precise method to minimize aberrations of mirror-based, wavelength-dispersive spectrometers for the extreme ultraviolet (XUV) and soft x-ray domain. The concept enables an enhanced resolving power E / Δ E , in particular, close to the diffraction limit over a spectral band of a few percent around the design energy of the instrument. Our optical element, the “diffractive wavefront corrector” (DWC), is individually shaped to the form and figure error of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The correction introduced by a suitable scheme converts an aberrated optics to pseudo-perfect optics which otherwise prevents achieving diffraction-limited focusing. A few schemes such as active bimorph mirrors (Mimura et al, 2010), refractive correctors (Sawhney et al, 2016;Seiboth et al, 2017), invariable-multilayer deposition (Matsuyama et al, 2018), diffractive wavefront correction (Probst et al, 2020) and layer stress controlling method (Cheng & Zhang (2019) have been demonstrated as tools for phase error corrections of different X-ray optical elements. Refraction-based correctors are thin, easy to insert into the beam path, do not change the optical axis and are straightforward to align.…”
Section: Introductionmentioning
confidence: 99%
“…The correction introduced by a suitable scheme converts an aberrated optics to pseudo-perfect optics which otherwise prevents achieving diffraction-limited focusing. A few schemes such as active bimorph mirrors (Mimura et al, 2010), refractive correctors (Sawhney et al, 2016;Seiboth et al, 2017), invariable-multilayer deposition (Matsuyama et al, 2018), diffractive wavefront correction (Probst et al, 2020) and layer stress controlling method (Cheng & Zhang (2019) have been demonstrated as tools for phase error corrections of different X-ray optical elements. Refraction-based correctors are thin, easy to insert into the beam path, do not change the optical axis and are straightforward to align.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest using an RZP on a spherical substrate, based on its theoretical description [5]. In comparison with an RZP on a planar substrate, it has evident advances, but is much more difficult to fabricate.…”
Section: Reflection Zone Plate On Curved Substratesmentioning
confidence: 99%
“…The RZPs were fabricated on a spherical substrate with a radius of curvature of 28.617 m. The substrate profile was carefully measured by two different methods, as was reported in [5]. The results, which we used for the correction of the RZP structure from aspheric and local slope (or figure) errors, provided a high spatial resolution.…”
Section: Optical Elementmentioning
confidence: 99%
See 2 more Smart Citations